The Attenuated Pseudorabies Virus Vaccine Strain Bartha K61: A Brief Review on the Knowledge Gathered during 60 Years of Research - Jonas L. Delva; Hans J. Nauwynck; Thomas C. Mettenleiter; Herman W. Favoreel (Pathogens, 2020)
Pseudorabies virus (PRV) is a member of the alphaherpesvirus subfamily of the herpesviruses and is the causative agent of Aujeszky’s disease in pigs, causing respiratory, neurological, and reproductive symptoms. Given the heavy economic losses associated with Aujeszky’s disease epidemics, great efforts were made to develop efficacious vaccines. One of the best modified live vaccines to this day is the attenuated Bartha K61 strain. The use of this vaccine in extensive vaccination programs worldwide has assisted considerably in the eradication of PRV from the domesticated pig population in numerous countries. The Bartha K61 strain was described in 1961 by Adorján Bartha in Budapest and was obtained by serial passaging in different cell cultures. Ever since, it has been intensively studied by several research groups, for example, to explore its efficacy as a vaccine strain, to molecularly and mechanistically explain its attenuation, and to use it as a retrograde neuronal tracer and as a vector vaccine. Given that the Bartha K61 vaccine strain celebrates its 60th birthday in 2021 with no sign of retirement, this review provides a short summary of the knowledge on its origin, characteristics, and use as a molecular tool and as a vaccine.